Heterologous expression of Thrombocidin-1 in Pichia pastoris: Evaluation of its antibacterial and antioxidant activity. (February 2019) - Yazdi, Farideh Tabatabaei; Tanhaeian, Abbas; Azghandi, Marjan; Vasiee, Alireza; Alizadeh Behbahani, Behrooz; Mortazavi, Seyed Ali; Roshanak, Sahar
Abstract: The antimicrobial peptide Thrombocidin-1 (TC-1) isolated from human blood that derived from NAP-2 by deleting of two amino acids from C-terminal region. In this study, a C-terminal 6 _ His tagged recombinant TC-1 was expressed as a secreted peptide in Pichia pastoris, for the first time. The recombinant P. pastoris was inoculated in to BMMY culture medium, incubation with 5 μl/ml absolute methanol for 72 h at 30 °C. The TC-1 peptide was concentrated with nickel affinity chromatography and electrophoresis on 16% acrylamide gels. The molecular weight of recombinant TC-1 is approximately 8 kDa and under these conditions, the concentration of TC-1 considered 190 μg/ml that determined by the Bradford method. The antimicrobial activity test (Minimum Inhibitory Concentration and Minimum Bactericidal Concentration) was done against: Listeria monocytogenes, Escherichia coli, Klebsiella pneumonia, Staphylococcus aureus, Enterococcus faecalis and Pseudomonas aeruginosa . The growth of these pathogenic bacteria was limited when we used peptide at a concentration of as low as 19.56 μg/ml. Based on DPPH radical scavenging (DPPH-RS) activity and reducing power assays, this peptide showed relatively good antioxidant potential in comparison with standard antioxidant used in this study (BHT). Due to the existence of TC-1 in blood, which makes it safe for human consumption, and the good results of its antimicrobial and antioxidant activity, it can be introduced as a good alternative and a novel effective peptide to food industry for bio-preservation. Highlights: P. pastoris can be used as a cell factory to produce antimicrobial peptides. Thrombocidin-1 showed high antimicrobial activity. Thrombocidin-1 showed high antioxidant activity. Due to the existence of TC-1 in blood, which makes it safe for human consumption, it can be used as a novel food preservative.